1996
DOI: 10.1116/1.588449
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of vinyltrimethylsilane with the Si(111)-(7×7) surface

Abstract: Vinyltrimethylsilane (vtms) serves as a ligand in the precursor molecule Cu(I)(vtms)(hfac) used in copper chemical vapor deposition. Investigations of the interaction of vtms with the Si(111)-(7×7) surface utilizing scanning tunneling microscopy, Auger electron spectroscopy, and thermal desorption spectroscopy (TDS) are reported. The adsorption is found to be highly site sensitive with an initial sticking coefficient most probably in excess of 0.03. With the exception of hydrogen, TDS spectra do not display vt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…While spectroscopic evidence presented above suggests that it binds quite [224], the similar type of addition on Si(111)-7×7 was not singled out by Andersohn et al [372]. Several surface reactions have been considered by this group but no spectroscopic evidence was presented and the paper largely focused on the thermal decomposition of vinyltrimethylsilane that leads to the formation of silicon carbide [372].…”
Section: Si(111)-7×7 Chemistry: Parallels Between Surface Dimers and mentioning
confidence: 91%
“…While spectroscopic evidence presented above suggests that it binds quite [224], the similar type of addition on Si(111)-7×7 was not singled out by Andersohn et al [372]. Several surface reactions have been considered by this group but no spectroscopic evidence was presented and the paper largely focused on the thermal decomposition of vinyltrimethylsilane that leads to the formation of silicon carbide [372].…”
Section: Si(111)-7×7 Chemistry: Parallels Between Surface Dimers and mentioning
confidence: 91%
“…In fact, the three-atom intermediate has been considered by Andersohn et al for VTMS on Si(111)-7×7. 5 It was demonstrated that VTMS adsorption onto the Si(111)-7×7 surface is site-specific. 5 VTMS interacts primarily with the center adatoms (most-depleted of negative charge), and the resulting adsorbed molecules are mostly immobile.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5 The experimental value of χ=0.75 for T =680 K and T =770 K was reported in Ref. 13. In this experiment, samples were prepared at a given temperature by deposition of ≈0.15 BL Si on the Si(111)7×7 surface followed by rapid quenching to room temperature.…”
mentioning
confidence: 97%